Examining the Impact of the COVID-19 Pandemic on Student Employability Skills - an Employer’s Perspective - Gibson van Mil, Lorraine; De-Pascale, Egizia; Burns, Emma; Scott, Fraser J.; Walker, Sarah E. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Like most university learners, students in the Department of Pure and Applied Chemistry at the University of Strathclyde, experienced hybrid learning environments from March 2020 transitioning into hybrid approaches for the full academic year 21/22. As students who were in the early years of their programme at this time, and experienced a shift from traditional education practices are soon to graduate, a short research project was undertaken to better understand the perception of employers on the impact of remote and hybrid learning on current, and future, graduate skills, and competencies. Several employers in the chemical industries were surveyed to rate changes in their perception of, and importance of, key graduate skills and competencies after the pandemic. In general, it was shown that the employers responding to this survey did not show concern about the level of personal, professional, and higher-level cognitive skills developed by students working in remote/hybrid environments during the pandemic. A gap in practical skills was acknowledged as indicated by employers’ viewing students as being less skilled in this area, however the skills gap was not thought to be important with regards to employability. Additionally, employers indicated an increased importance on a student’s ability to develop and demonstrate basic personal and professional skills including communication, collaboration, interpersonal/networking, autonomy, self-management, and resilience. The research suggests programme leaders creating or modifying curricula should place attention on the development of these skills and competencies to ensure students are self-led to successfully transition into the workplace.